IOT Based Condition Monitoring of Electric Machinery - Samanta, S; Bhattacharyya, S; Mukherjee, D (International Journal of Computer Sciences and Engineering, 2025)
This paper presents the scheme of a remote monitoring system for electric machines based on Internet of Things (IoT) technology for safe and economic data communication in industry. To make the system fast and user friendly, authors have developed dedicated software in JAVA platform by which the authorized person can monitor the condition of all remotely located machines from an industry via a common server. A module of sensors monitor the parameters like voltage, current, speed, temperature etc. and the server records run time data of all machines and observes the performance of every machine. The authorized person can check the database when required on that day from the server. For any unwanted situation, the software module send a SOS message along respective fault information to that authorized person’s mobile whether he/ she will be present or not present in control room.